Information and Communication Technology-Enhanced Business and Managerial Communication in SMEs in the Czech Republic - Marcel Pikhart; Blanka Klimova (Information, 2020)
Current managerial communication in the global business world has recently experienced dramatic and unprecedented changes connected to the use of Information and Communication Technology (ICT) in business and managerial communication. The objective of this paper is to analyze the changes in ICT-enhanced business and managerial communication in Small and Medium Enterprises (SMEs) in the Czech Republic. The use of ICT in business and managerial communication is obvious and brings various benefits, but it also has some drawbacks that should be identified and analyzed. From a methodological point of view, this study is twofold. Firstly, we conduct a systematic review of the current literature on the topic of business and managerial communication, providing an understanding of the recent development in the area of business and managerial communication. Secondly, we conduct qualitative research into the current state of ICT-enhanced managerial and business communication in several SMEs in the Czech Republic. The findings of the literature research show that there are two key aspects that define modern business and managerial communication, i.e., interculturality and interconnectedness. These two aspects of business and managerial communication are very recent, and they bring many challenges that must be considered in order to optimize communication. These altered communication paradigms have the potential to improve global competitiveness and produce new opportunities in the global market. The second part of the research shows that the general awareness of the changes in business communication is limited, and this could potentially pose a threat to business and managerial communication, leading to a loss of opportunities and reduced competitiveness. The majority of global-based companies have already become culture-, communication-, technology- and information-dependent, and ignoring or neglecting this fact presents a significant risk, which may be one of the biggest threats to global competitiveness. Since the success of SMEs is critical for the development of the national economy, it is recommended that company communication be continuously enhanced by frequent training at all organizational levels. This presents a challenge for educational institutions and training centers, managers and businesspeople, of creating communication competencies that would be highly rewarded in the global business environment.